Faktor-Faktor yang Berhubungan dengan Pemilihan Kontrasepsi di Puskesmas Rambah Samo Kabupaten Rokan Hulu - Syukaisih . (Jurnal Kesehatan Komunitas, 2015)
Rate of population growth about 1.49% in 2010. This could affect the development so that the necessary policies to limit it. Therefore, the Government dock program Long-Term Contraception Method (LTM). But the reality LTM as Medical Operations Men (MOP), Medical Surgery Women (MOW) and Intra Uterine Device (IUD) / spiral, still less desirable implant acceptors of family planning (KB). The majority of acceptors prefer hormonal birth control methods such as injections and pills. Purpose of this study was to determine the factors related to the choice of contraception in Puskesmas Rambah Samo Rokan Hulu 2011. The study was cross sectional method. The population is 3134 people with research subjects throughout acceptors active in Puskesmas Rambah Samo were 96 respondents with accidental sampling. Data were collected using a questionnaire. Data were analyzed using a statistical test Chi-Square with a degree of confidence (p) <0.05. The results showed that the acceptors most choose to use contraceptives kind non MKJP by 56.2%. Factors related to the selection of contraceptives at the health center Rambah Samo Rokan Hulu in 2011 is the education factor (p value = 0.037), knowledge (p value = 0,000), information (p value = 0.000). While the factors that are not related to the choice of contraception is the age factor (p value = 0.897). Suggested to Puskesmas Rambah Samo and Women Empowerment and Family Planning (BPPKB) improve counseling knowledge through Health Promotion and motivation of health through IEC (Communication, Information, and Education) regarding family planning and contraception as an effort to increase public knowledge about family planning and contraception itself